1998
DOI: 10.1038/sj.gt.3300711
|View full text |Cite
|
Sign up to set email alerts
|

Sustained transgene expression in vitro and in vivo using an Epstein–Barr virus replicon vector system combined with HVJ liposomes

Abstract: For long-term gene expression in tissues, we constructed chromosomally in BHK-21 cells. In human cells, transforman Epstein-Barr virus (EBV) replicon-based plasmid, pEB, ation was five to 20 times more efficient with pEBc than containing the latent viral DNA replication origin (oriP) and with pcDNA3, and 18-35% of the introduced EBV replicon EBV nuclear antigen-1 (EBNA-1). When pEB was transplasmid was replicated autonomously. The luciferase gene ferred to human cells (HeLa-S3, HEK 293 and FS 3) and or lacZ ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 31 publications
1
55
0
Order By: Relevance
“…The one disadvantage of the vector is, as shown in this study, transient transgene expression. However, recent studies showed that the combination of EpsteinBarr virus (EBV) replicon vector based on the plasmid resulted in sustained gene expresion in nonlymphocytic cultured cells and the mouse liver; 27 thus we are now assessing the sustained gene expression using an EBV replicon vector in a similar animal model. In summary, we developed a method for gene transfer using electronic pulse, an approach which proved to be safe and more efficient than that using naked DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The one disadvantage of the vector is, as shown in this study, transient transgene expression. However, recent studies showed that the combination of EpsteinBarr virus (EBV) replicon vector based on the plasmid resulted in sustained gene expresion in nonlymphocytic cultured cells and the mouse liver; 27 thus we are now assessing the sustained gene expression using an EBV replicon vector in a similar animal model. In summary, we developed a method for gene transfer using electronic pulse, an approach which proved to be safe and more efficient than that using naked DNA.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently found that these functions actually work in rodent cells, at least in some in vitro experimental systems (Kishida et al, unpublished observations). Also, Saeki et al, 32 Kaneda et al, 33 and Nishizaki et al 30 have shown that the EBVbased plasmid vector enabled significantly prolonged expression of marker genes in rodent organs that had been transfected by means of HVJ-liposomes 32,33 or a gene gun. 30 Taking into account the potential application of naked pDNA injection to gene therapy, constant and persistent expression is desired.…”
Section: Gl3 and Pggl3 (Student's T Test)mentioning
confidence: 99%
“…The application of this plasmid in various cells has been developed. [10][11][12] EBV is of particular interest as a vector because of its latent infection property, which is characterized by autonomous replication and nuclear retention of the EBV genome in host cells. 13 The persistent maintenance of the EBV genome has been analyzed in depth and is mediated by the replication origin of the latent viral DNA (oriP) and EBV nuclear antigen 1 (EBNA-1).…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Previously, our group showed that use of the EBV replicon vector leads to sustained transgene expression in vivo in the liver. 11 With regard to efficient vector delivery, numerous viral and nonviral vectors have been developed. 4 Adenovirus-mediated gene transfer has been successful in transiently expressing transgenes, but it also causes undesired effects such as hepatic inflammation.…”
Section: Introductionmentioning
confidence: 99%